Biochar for remediation of agrochemicals and synthetic organic dyes from environmental samples: A review - Gautam R.K.; Goswami M.; Mishra R.K.; Chaturvedi P.; Awashthi M.K.; Singh R.S.; Giri B.S.; Pandey A. (My University, 2025)
Application of agrochemicals in farming sector to control insects and pests; and use of synthetic organic dyes to color the products are increasing continuously due to the rapid growth of industries. During the application process many industries releases toxic agrochemicals and dyes in to the aquatic environment and on land without the proper treatment. Due to their toxicity the disposal of such chemicals is of utmost importance. Biochar offers the ability to remediate these substances from environmental matrices because of their high sorption ability of pollutants from water and soil. This review highlights the development and advancement of biochar-based treatment for abatement of agrochemicals and synthetic organic dyes, involving its technical aspects and the variables connected with removing these kinds of pollutants. Several optimization parameters like temperature, pH, chemical concentration, biochar properties, time, and co-existing ions have been elaborated. Literature survey shows that most of the researches on biochar application have been conducted in the batch mode. Hence there is an urgent need to apply this beneficial technique for the remediation of pollutants at the larger scale in the real water and soil samples. A comprehensive summary on sorption kinetics and adsorption isotherms with regards to pollutant removal is also presented. This review also covers the cost analysis of various techniques where biochar has been used as an adsorbent. Thus this review makes an easy roadmap for the further development in biochar and biochar based composites and expansion of these demanding areas of research in biochar and their applications. © 2021